2022
DOI: 10.1158/1078-0432.ccr-21-1846
|View full text |Cite
|
Sign up to set email alerts
|

A Novel Role for DNA-PK in Metabolism by Regulating Glycolysis in Castration-Resistant Prostate Cancer

Abstract: Purpose: DNA-dependent kinase catalytic subunit (DNA-PKcs, herein referred as DNA-PK) is a multifunctional kinase of high cancer relevance. DNA-PK is deregulated in multiple tumor types, including prostate cancer (PCa), and is associated with poor outcomes. DNA-PK was previously nominated as a therapeutic target and DNA-PK inhibitors are currently undergoing clinical investigation. While DNA-PK is well studied in DNA repair and transcriptional regulation, much remains to be understood about the way by which DN… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
17
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(18 citation statements)
references
References 58 publications
1
17
0
Order By: Relevance
“…Interestingly, upstream stimulatory factor (USF) 1/2 heterodimer has been shown to be phosphorylated by DNA-PKcs resulting in fatty acid synthase (FASN) promoter activation ( Wong et al, 2009 ). Consistent with this, Dylgjeri et al (2022) have also found FASN as one of the novel DNA-PK partners, indicating an essential role of DNA-PKcs in regulating the cellular metabolism.…”
Section: Transcription Regulation By Dna-pkcssupporting
confidence: 70%
See 2 more Smart Citations
“…Interestingly, upstream stimulatory factor (USF) 1/2 heterodimer has been shown to be phosphorylated by DNA-PKcs resulting in fatty acid synthase (FASN) promoter activation ( Wong et al, 2009 ). Consistent with this, Dylgjeri et al (2022) have also found FASN as one of the novel DNA-PK partners, indicating an essential role of DNA-PKcs in regulating the cellular metabolism.…”
Section: Transcription Regulation By Dna-pkcssupporting
confidence: 70%
“…While we have long been appreciating the role of DNA-PKcs in DNA DSB repair mechanism, recent evidence highlighting a significant amount of DNA-PKcs being present in the cytoplasm ( Dylgjeri et al, 2022 ) suggests the novel role of DNA-PKcs in cells. By performing DNA-PK protein interactome, Dylgjeri et al (2022) have reported novel interacting partners of DNA-PK, including those involved in ribonucleic acid metabolism (DOT1L [histone methyltransferase], RPLs [L ribosomal proteins], HNRPs [heterogeneous nuclear ribonucleoprotein Ks], eEFs [eukaryotic elongation factors]), energy metabolism (PGK1, PKM2, FASN, VDAC-2 [voltage-dependent anion channel-2]), heat shock proteins (HSPs), zinc finger proteins (ZNFs), and inflammation (MIF [macrophage migration inhibitory factor]). This suggests that inhibition of DNA-PK is likely to inhibit multi-substrates at multiple locations (nucleus and cytoplasm), which may yield a complex outcome.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…DNA-PKcs, when present in the nucleus contributes to repair and the regulation of transcription, but in the cytoplasm [63], it also has functions in energy metabolism [64], fatty acid synthesis [65] and aging [66]. Although the functions of DNA-PKcs continue to expand [67], its involvement in c-NHEJ has received the most attention and has been profoundly enriched by recent structural studies revealing intriguing aspects of its function in this repair pathway [68,69]. The work presented here helps to further develop and consolidate the functions of DNA-PKcs related to resection.…”
Section: Discussionmentioning
confidence: 99%
“…Metabolically, PKM2 has reduced enzymatic activity and slows down pyruvate production, allowing more upstream biomolecules to be available for other biosynthetic processes [ 137 ]. A recent report suggests that deoxyribonucleic acid (DNA)-dependent protein kinase (DNA-PK) may play a role in regulating increased glycolytic flux by phosphorylating aldolase and PKM2 to increase their enzymatic activities [ 138 ]. Interestingly, PKM2 also possess non-metabolic kinase activity and can function as a transcription factor, thereby promoting metastasis and regulating responses to hypoxia in PCa [ 139 , 140 , 141 , 142 , 143 ].…”
Section: Major Bioenergetic Sourcesmentioning
confidence: 99%